Developing change leaders : the principles and practices of change leadership development - Aitken, Paul; Higgs, Malcolm (Butterworth-Heinemann ; : Elsevier, 2010)
Tackles the question of how to develop effective change leaders who make a difference to organizational life. Based on the authors' real-life experience of designing development programmes and coaching individual change leaders, this book helps you to assess your readiness for leading change and develop the skills to make change successful.